Sustainable Development Strategies for Environmentally Vulnerable Regions: Collaborative Governance Framework in Ketam Island - Annisa Ilmi Faried; Dian Septiana Sari; Rahmad Sembiring; Saimara Sebayang; Nor Harlinda Binti Harun; Nisa Ulzannah (International Journal of Management, Economic and Accounting, 2025)
This investigation examines participatory development approaches specifically designed for ecologically sensitive regions, utilizing Ketam Island as the primary research setting. The methodology incorporates stakeholder engagement protocols combined with environmental sustainability assessment frameworks. Findings demonstrate that integrated multi-actor strategies significantly enhance both conservation outcomes and economic resilience indicators. Analysis reveals successful deployment of community-based governance mechanisms that effectively balance environmental preservation priorities with socioeconomic development requirements. Results indicate that participatory governance structures provide viable pathways for achieving dual objectives of ecological protection and community prosperity in vulnerable marine ecosystems. Implications extend to policy development for comparable island communities confronting similar sustainability challenges across Southeast Asia's coastal regions.